The efficacy of terminology-extraction systems for the translation of documentaries. - Hanoulle, Sabien; Hoste, Véronique; Remael, Aline (Perspectives: Studies in Translatology, 2015)
This article investigates whether the integration of a domain-specific, bilingual glossary supports audiovisual translators of documentaries in terms of translation process time and terminological errors. After a short review of issues typical of documentary translation and a discussion of the use of translation-memory software in general, the reference corpora are described. Next, a manually labeled glossary is created and its constitution is explained with special emphasis on the criteria used to qualify what a ‘term is, or is not’. This glossary is then used as a gold standard to calculate the rate of agreement with the glossary of three automatic terminology-extraction systems. Finally, experiments with Master's students demonstrate how both glossaries (the gold standard and one automatically extracted glossary) reduce their process time significantly but not the number of terminological errors. The article concludes with a discussion of the data analysis and by presenting the next step in this research, i.e. experiments with professional translators and further challenges such as a comparison between the glossaries.